Effect of two different dentin desensitizers on shear bond strength of two different bonding agents to dentin: An in vitro study - Shekhar Bhatia; Manjunath Mysore Krishnaswamy (Wolters Kluwer Medknow Publications, 2012)
Objective: The objective of the study was to compare the effect of two different desensitizers on shear bond strength of two different fifth-generation single-bottle adhesive agents on dentin surface. Materials and methods: Sixty human premolars were taken and divided into six groups of 10 samples each. The first two groups were the control groups and were not pretreated with any desensitizer; the remaining four groups were the experimental groups and were pretreated with either Denshield™ or Sensodent-K™ desensitizer. The specimens in each group were subjected to acid etching, application of adhesive (Single Bond or Prime and Bond NT), and application of hybrid composite resin (Z-100) according to the standard protocol. The specimens were subjected to shear bond strength testing, using a Lloyds universal testing machine (EZ20), followed by stereomicroscopic evaluation of the fracture mode at the debonded interface. Results: Statistically significant difference existed between the two bonding agents in the control groups (group 1 and 2), with Prime and Bond NT showing higher bond strength than Single Bond. No statistically significant difference existed between either control or pretreated with any desensitizer when either of the adhesive systems was used. Prime and Bond NT showed statistically higher bond strength value when teeth were pretreated with Sensodent-K™ (groups 5 and 6). No statistically significant difference in bond strength values were observed between the bonding agents when pretreated with Denshield™ desensitizer.